2021
DOI: 10.1021/acsaem.1c01863
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Sb Pillared Few-Layered Ti3C2Tx MXenes for Advanced Sodium Storage

Abstract: Pillaring technology has proven to be an effective strategy to improve the electrochemical performance of MXenebased composites, especially the rate performance due to the enlarged interlayer spacing. Taking the larger radius of sodium ions into account, it is urgent to develop pillared MXene-based composites for sodium-ion batteries (SIBs). To fully deliver high rate performance of pillared MXenes and high capacity of Sb in SIBs, in this work, we exquisitely decorate ultrafine Sb particles onto flexible few-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 77 publications
2
15
0
Order By: Relevance
“…The potential profile, current peak and the associated potentials (vs Na/Na + ) in the first sodiation half cycle are also likely to be partly influenced by the formation of SEI layer, although that seems to have been minimized here, because of the presence of fairly coarse electrode-active (Sb) particles (and, hence, low electrode/electrolyte interfacial area). The above aspects seem to be in agreement with other previous reports, where SEI formation occurs in the very first sodiation half cycle at a relatively higher potential, with respect to that corresponding to the initiation of sodiation of Sb, followed by the conversion of metallic Sb to Na 3 Sb at lower potentials. Based on the literature related to sodiation/desodiation pathway(s) of Sb, Sb/oxide composites and the observations made here (with the CVs and chronopotentiograms), it is likely that during desodiation Na 3 Sb gets converted first to Na 1.7 Sb and then to cSb, along with some amorphous phase(s), such as aSb or aNa 1.0 Sb.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The potential profile, current peak and the associated potentials (vs Na/Na + ) in the first sodiation half cycle are also likely to be partly influenced by the formation of SEI layer, although that seems to have been minimized here, because of the presence of fairly coarse electrode-active (Sb) particles (and, hence, low electrode/electrolyte interfacial area). The above aspects seem to be in agreement with other previous reports, where SEI formation occurs in the very first sodiation half cycle at a relatively higher potential, with respect to that corresponding to the initiation of sodiation of Sb, followed by the conversion of metallic Sb to Na 3 Sb at lower potentials. Based on the literature related to sodiation/desodiation pathway(s) of Sb, Sb/oxide composites and the observations made here (with the CVs and chronopotentiograms), it is likely that during desodiation Na 3 Sb gets converted first to Na 1.7 Sb and then to cSb, along with some amorphous phase(s), such as aSb or aNa 1.0 Sb.…”
Section: Resultssupporting
confidence: 93%
“…The above aspects seem to be in agreement with other previous reports, where SEI formation occurs in the very first sodiation half cycle at a relatively higher potential, with respect to that corresponding to the initiation of sodiation of Sb, followed by the conversion of metallic Sb to Na 3 Sb at lower potentials. Based on the literature related to sodiation/desodiation pathway(s) of Sb, Sb/oxide composites and the observations made here (with the CVs and chronopotentiograms), it is likely that during desodiation Na 3 Sb gets converted first to Na 1.7 Sb and then to cSb, along with some amorphous phase(s), such as aSb or aNa 1.0 Sb. Accordingly, the second and subsequent sodiation half cycles also involved sodiation of some aSb, in addition to cSb.…”
Section: Resultssupporting
confidence: 93%
“…27 However, when they are used as an anode electrode material for rechargeable batteries, MXene nanosheets usually suffer from aggregation and the self-restacking effect during the cycling process, which affects the ion transport properties, leading to lowered capacities, rate capabilities and cycling stabilities. 28,29 Recently, an effective strategy has been proposed to overcome this shortcoming by fabricating pillared MXene structures with enlarged interlayer spacing. Lu et al found that the intercalation of Al ions in a two-dimensional Ti 3 C 2 T x anode increased the spacing of the MXene layers by about 0.1 nm, and the lithium storage capacity and cycling stability of the MXene anode were also significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…), [31] supercapacitors, [32] electrocatalyst, [33] photocatalyst, [34] field-effect transistor, [35] electromagnetic shielding, [36] seawater desalination [37] and other fields have broad application prospects.However, the disadvantages of MXenes, such as low flexibility, easy stacking, and poor stability in oxygen environment, greatly limit the further development of pristine MXenes. [38,39] In recent years, inspired by the elemental doping mechanism of graphene, [40][41][42] optimizing pristine MXene properties (such as electronic, optical, magnetic, etc.) by elemental doping methods has been shown to be an effective strategy.…”
mentioning
confidence: 99%
“…However, the disadvantages of MXenes, such as low flexibility, easy stacking, and poor stability in oxygen environment, greatly limit the further development of pristine MXenes. [38,39] In recent years, inspired by the elemental doping mechanism of graphene, [40][41][42] optimizing pristine MXene properties (such as electronic, optical, magnetic, etc.) by elemental doping methods has been shown to be an effective strategy.…”
mentioning
confidence: 99%